New genera, species and combinations in the Pseudomicrocara Armstrong group (Coleoptera: Scirtidae) based on morphology supported by mitochondrial and nuclear gene sequence data - Watts, C.h.s.; Cooper, S.j.b.; Libonatti, M.l. (Zootaxa, 2020)
The Australian Scirtidae genus Pseudomicrocara Armstrong, previously shown to be polyphyletic, is revised using both morphology and sequence data from the mitochondrial gene cytochrome oxidase subunit 1 and two nuclear genes, elongation factor 1-alpha and topoisomerase. Twenty-three genera, 16 of which are new, are recognised based on morphology, primarily of the mandibles and maxillary palpi, and male and female genitalia. Maximum likelihood and Bayesian phylogenetic analyses were used to examine relationships among species from 21 of the 23 recognised genera. Fifteen of the genera were recovered as distinct lineages. A further six, Accolabass Watts, Anocyphon gen. nov., Copiacyphon gen. nov., Nasutuscyphon gen. nov., Pseudomicrocara and Saprocyphon gen. nov. were considered to be genera based on both morphology and phylogenetic analysis but their species composition is uncertain and will require more work to confirm. The 17 new genera are fully described, keys are provided to all the genera in the Pseudomicrocara group, and to all the species in the genera Copiacyphon gen. nov., Spilotocyphon gen. nov., Accolabass Watts, Saltuscyphon gen. nov. and Vadumcyphon gen. nov. The male aedeagi of all new genera and species are illustrated, as are the female prehensors of some species. The following genera are described as new: Alpestriscyphon gen. nov., Anthocara gen. nov., Anocyphon gen. nov., Copiacyphon gen. nov., Furcacyphon gen. nov., Latuscara gen. nov., Pictacara gen. nov., Nasutuscyphon gen. nov., Nektriscyphon gen. nov., Pumiliocara gen. nov., Ruborcara gen. nov., Saltuscyphon gen. nov., Saprocyphon gen. nov., Sisyracyphon gen. nov., Spilotocyphon gen. nov., Tenebriocyphon gen. nov. and Vadumcyphon gen. nov. A total of 45 new combinations are proposed. The following species are described as new: Accolabass monteithi sp. nov.; Alpestriscyphon bartlefrere sp. nov., Al. spurgeon sp. nov.; Anocyphon lepus sp. nov.; Copiacyphon brindaleensis sp. nov., C. cardinalis sp. nov., C. dytikos sp. nov.; Pumiliocara peneparva sp. nov.; Ruborcara saintae sp. nov.; Saltuscyphon montanus sp. nov., Sal. teraniaensis sp. nov.; Saprocyphon bithongensis sp. nov.; Sisyracyphon brisbanensis sp. nov., S. bulburinensis sp. nov.; Spilotocyphon occidentalis sp. nov., Sp. orientalis sp. nov., Sp. zwicki sp. nov.; Vadumcyphon centralis sp. nov., V. rugosus sp. nov. A checklist of all Australian taxa in the redefined Pseudomicrocara group is included. Sequence data of the Argentinian species Pseudomicrocara antarctica (Fairmaire) is included. Phylogenetic analyses place this species as a distinct lineage within the Pseudomicrocara group.